Re-carbonized vitreous carbon substrates for optical applications. (April 2015) - Nascimento, F; Damião, A J; Santos, M V R; Origo, F D; Reis, J F; Trevenzolli, L; Gaspar, A C M; Baesso, J
Abstract: Imaging optical systems components for satellites must have low specific mass and high stiffness, as weight is a problem for payloads and stiffness is essential to keep the substrate front surface shape. In this work, Re-carbonized Vitreous Carbon (RVC) was tested as a substrate material. The process to obtain RVC is different from the traditional process to obtain the Monolithic Vitreous Carbon (MVC). It is essential to understand the process to evaluate the surface roughness data. This work describes the process to obtain RVC, as a candidate for optical component substrate, and the results of its surface roughness measurements.